RANCANGAN PENATAAN ARSIP KARYA SENI PERTUNJUKAN UNTUK MENDUKUNG PENGEMBANGAN TRIDHARMA PERGURUAN TINGGI DI ISI SURAKARTA - Wahyu Widyasih (Arsip Universitas Gadjah Mada, 2022)
This study aims to identify the types of art archives and arrange their arrangement designs in order to support the development of the tridharma of higher education at the Indonesian Institute of the Arts (ISI) Surakarta. The archives studied are the archives of performing arts that are the result of the Tridharma organization. The research was conducted using a qualitative descriptive method. That is describing a situation based on the facts that appear. The results of field observations show that the performing arts document consists of text, audio, and video. Its creation cannot be separated from previous works of art as a reference or source of works of art. Artwork documents are archives because they are the result of the tridharma process, but have only been managed as a library. The archives are dominated by final works of art from study programs at the Faculty of Performing Arts, results of artistic research from the Research Centre, and results of community service works of art from the Centre for Community Service. ISI Surakarta Archives Retention Schedule stipulates the archive as a static archive (permanent) after the retention period expires. Its arrangement requires a design according to archival standards. The design is made by taking into account the principle of provenance and original order. The design includes archive creators, archive classification (final project reports, research, and community service), archive indexes (reports, audio visual recordings, and intellectual property certificates), archive cross-linking to link different types of archives for the same archive, information archives, access conditions and archive service procedures. Keywords: archive, arrangement, design, performing arts, tridharma